2008
DOI: 10.1021/om701171y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structures of Scandium and Lutetium Benzyl Complexes

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 38 publications
(21 reference statements)
2
48
0
Order By: Relevance
“…Other rare solid‐state structures of monomeric but heteroleptic Tp‐based rare‐earth‐metal complexes as [Tp R,R Ln(Danip)(CH 2 SiMe 3 )] (R=Me or R=H, Ln=Yb, Danip=2,6‐di( o ‐anisol)phenyl)) display similar bond lengths (Yb−C ipso : 2.414(3)–2.438(4)/2.402(4)–2.435(5) Å; Yb−C(neosilyl): 2.379(4)–2.392(4)/2.359(4)–2.368(4) Å) taking into account the metal‐ion size . The Lu−C(benzyl) bond length (2.412(3) Å) in 9‐Lu matches that in Lu(CH 2 Ph) 3 (THF) 3 (2.404(7)–2.413(5) Å) and Lu(CH 2 Ph) 3 (THF) 2 (2.380(3)–2.404(3) Å) but is slightly elongated compared with Cp*Lu(CH 2 Ph) 2 (THF) (2.378(2)–2.386(2) Å; Cp*=C 5 Me 5 ) . Furthermore, there is no significant secondary interaction between Lu1 and the ipso carbon atom C27 for 9‐Lu , as suggested by the Lu1⋅⋅⋅C27 distance of 3.314 Å and the Lu‐C(CH 2 )‐C27 angle (114.3(2)°).…”
Section: Resultsmentioning
confidence: 64%
“…Other rare solid‐state structures of monomeric but heteroleptic Tp‐based rare‐earth‐metal complexes as [Tp R,R Ln(Danip)(CH 2 SiMe 3 )] (R=Me or R=H, Ln=Yb, Danip=2,6‐di( o ‐anisol)phenyl)) display similar bond lengths (Yb−C ipso : 2.414(3)–2.438(4)/2.402(4)–2.435(5) Å; Yb−C(neosilyl): 2.379(4)–2.392(4)/2.359(4)–2.368(4) Å) taking into account the metal‐ion size . The Lu−C(benzyl) bond length (2.412(3) Å) in 9‐Lu matches that in Lu(CH 2 Ph) 3 (THF) 3 (2.404(7)–2.413(5) Å) and Lu(CH 2 Ph) 3 (THF) 2 (2.380(3)–2.404(3) Å) but is slightly elongated compared with Cp*Lu(CH 2 Ph) 2 (THF) (2.378(2)–2.386(2) Å; Cp*=C 5 Me 5 ) . Furthermore, there is no significant secondary interaction between Lu1 and the ipso carbon atom C27 for 9‐Lu , as suggested by the Lu1⋅⋅⋅C27 distance of 3.314 Å and the Lu‐C(CH 2 )‐C27 angle (114.3(2)°).…”
Section: Resultsmentioning
confidence: 64%
“…The C‐P‐N‐Sc four‐membered ring is nearly coplanar with the N3‐Sc‐C1 and N3‐P‐C1 angles of 77.93(10)° and 98.75(12)°, respectively. The Sc−C1 distance (2.284(3) Å) is longer than the Sc−C bonds in complex 2 (2.205(3) Å on average), but close to those in Sc(CH 2 Ph) 3 (THF) 3 (2.311(3) Å on average) . The Sc−N3 distance (2.014(2) Å) is close to those in the scandium anilido complexes, such as [{ t BuCN(DIPP)} 2 CHSc(NH(DIPP))(CH 3 )] and [CH 3 C{N(DIPP)}CHC(CH 3 )(NCH 2 CH 2 NMe 2 )(CH 3 )Sc(NH(DIPP))(CH 3 )] (2.047(3) Å) .…”
Section: Methodsmentioning
confidence: 79%
“…43,59,78 (NN fc ): Initially, we sought out to employ salt metathesis between K 2 (NN fc ) and MX 3 (THF) y (M = rare-earth metal, X = Cl or Br, y = 3-4) and found that the reaction was poorly reproducible and usually accompanied by a side product, the bis-ligand-adduct K[(NN fc ) 2 M], which was difficult to remove. 81 At the same time, we and other groups independently published protocols to prepare key metal benzyl synthetic intermediates, M(CH 2 Ar) 3 (M = Sc, Y, La, and Lu, Ar = Ph, 3,5-C 6 H 3 Me 2 ), from MX 3 (X = Cl, Br), [95][96][97][98] which, in turn were obtained directly from metal oxides. 99 The acidbase reaction between M(CH 2 Ar) 3 41,46 This in situ method was much more efficient: the preparation time was reduced to 1 day from 1 week and the overall yield was improved for all rare-earth metals, Scheme 2a.…”
Section: B Synthesis Of Rare-earth Metal Complexes Supported By Ferrmentioning
confidence: 99%